2023
DOI: 10.1177/09544070231167616
|View full text |Cite
|
Sign up to set email alerts
|

Model based integrated control strategy for effective brake energy recovery to extend battery longevity in electric two wheelers

Abstract: This study aims to achieve optimal regenerative braking performance in the form of a reduced decline in battery SOC for a BLDC electric machine with peak torque of 10 Nm for use in electric two-wheelers. This is conducted via a comparison of control algorithms based on Direct Look-up table, Fuzzy Logic and their combination with PID control. The whole vehicle model and the energy recovery control strategies are designed using MATLAB Simulink by benchmarking the design with the parameters of the Ola Electric S1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Heydari et al[102], and Gang et al[105] was less than 15%. The energy re efficiency of Wu et al[92], Ashok et al[95], Liu et al[96], Sandrini et al[97], Chu[98], Ji et al[103], and He et al[104] exceeded 20%, with Liu et al[96] having an recovery efficiency of over 45%.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Heydari et al[102], and Gang et al[105] was less than 15%. The energy re efficiency of Wu et al[92], Ashok et al[95], Liu et al[96], Sandrini et al[97], Chu[98], Ji et al[103], and He et al[104] exceeded 20%, with Liu et al[96] having an recovery efficiency of over 45%.…”
mentioning
confidence: 93%
“…It can be seen that the energy recovery efficiency of He et al [10], Yang et al [11], Jiang et al [21], Geng et al [26], Ning et al [27], Zhao et al [28], Li et al [70], Yin et al [93], Chen et al [94], Shang et al [98], Chang et al [99], Chun et al [100], Liu et al [101], Heydari et al[102], and Gang et al[105] was less than 15%. The energy recovery efficiency of Wu et al[92], Ashok et al[95], Liu et al[96], Sandrini et al[97], Chun et al[98], Ji et al[103], and He et al[104] exceeded 20%, with Liu et al[96] having an energy recovery efficiency of over 45%.…”
mentioning
confidence: 94%
“…The energy recovery of regenerative braking can be improved by up to 9.62%. Ashok et al [32] showed that the fuzzy PID control strategy performs well in the energy recovery of electric two-wheeled vehicles, with an energy recovery rate of 44%. Liu et al [33] adopted an adaptive braking force distribution control strategy.…”
Section: Introductionmentioning
confidence: 99%